2018
DOI: 10.1007/s00285-018-1223-0
|View full text |Cite
|
Sign up to set email alerts
|

Getting in shape and swimming: the role of cortical forces and membrane heterogeneity in eukaryotic cells

Abstract: Recent research has shown that motile cells can adapt their mode of propulsion to the mechanical properties of the environment in which they find themselves – crawling in some environments while swimming in others. The latter can involve movement by blebbing or other cyclic shape changes, and both highly-simplified and more realistic models of these modes have been studied previously. Herein we study swimming that is driven by membrane tension gradients that arise from flows in the actin cortex underlying the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 77 publications
0
28
0
1
Order By: Relevance
“…This has been modeled and analyzed [28], and it was shown how characteristics of the protrusions, such as their height, affect the swimmer's speed and efficiency. In addition, it is also known that Dicty cells can swim for several cell lengths without shape changes [29], and it has been shown that they can do so by creating an axial tension gradient in the membrane [17].…”
Section: The Primary Modes Of Cell Movementmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been modeled and analyzed [28], and it was shown how characteristics of the protrusions, such as their height, affect the swimmer's speed and efficiency. In addition, it is also known that Dicty cells can swim for several cell lengths without shape changes [29], and it has been shown that they can do so by creating an axial tension gradient in the membrane [17].…”
Section: The Primary Modes Of Cell Movementmentioning
confidence: 99%
“…It is thought that a gradient of cortical density and myo-II generates both the cortical flow and an axial pressure gradient in both morphologies, but what initiates the flow remains undetermined [168]. Computations reported in Wu et al [17] show that tension gradients in the cortex can generate large-scale flows sufficient to carry monomers anteriorly, and thus can provide another mechanism for polarization by segregating components via the flow.…”
Section: The Role Of Membrane and Cortical Tension In Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…69,186,187 Computational results from a model using a free-energy-based description of the membrane shows that cells can swim under various combinations of tension gradient in the membrane and heterogeneity of the bending rigidity. 69 Moreover, the direction of migration depends on the balance between the cortical tension gradient and the variation of the bending rigidity. This provides an explanation of the observation that some cells move using a small cap in the front, while other cells move with the large bleb in front.…”
Section: Figure 12mentioning
confidence: 99%